(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
Quantitative analysis on the planktonic foraminiferal assemblages in the Late Pliocene - Early Pleistocene segment of the Capo Rossello section evidences the same number of relative abundance fluctuations of the Globigerinoides ruber taxonomic unit recorded in the same stratigraphic interval of other Mediterranean sequences. Between the Globorotalia inflata FO and the Discoaster brouweri LO 4 relative abundance fluctuations are present. Since the D. brouweri LO is recorded in the Mediterranean basin below the base of the Olduvai magnetic event and in coincidence of relative abundance fluctuation 73, the Gt. inflata FO is coincident with fluctuation 80. The first appearance ol Globorotalia truncatulinoides is recorded on the second fluctuation above the Gt. inflata FO and on the second fluctuation below the D. brouwueri LO. Therefore the Gt. truncatulinoides FO is coincident with fluctuation 77. The absolute age proposed for these 3 bio-events is 1.99,2.07 and 2.13 MA respectively. The most important calcareous nannofossil events, recognized by quantitative analysis, have been correlated to the abundance fluctuations of the Globigerinoides ruber taxonomic unit.